ICT Integration and Teaching Effectiveness in Public Primary Schools in Bagamoyo District, Tanzania - Mzee Maalim; Prospery Mwansa Mwila (Action Research Journal Indonesia (ARJI), 2026)
Information and Communication Technology (ICT) is increasingly recognised as a catalyst for improving teaching effectiveness and students' learning outcomes. Despite Tanzania’s investments in digital education through policy reforms, teacher training, and ICT infrastructure, effective classroom integration remains constrained by inadequate infrastructure, limited pedagogical competencies, and unequal access to digital resources. This study assessed the impact of ICT integration on teaching effectiveness, students' learning outcomes, motivation, engagement, and educational equity in selected public primary schools in Bagamoyo District, Tanzania. A mixed-methods approach using a convergent parallel design was adopted. Data were collected from teachers, head teachers, and education officers using questionnaires, interviews, and observation checklists, and analysed using descriptive and inferential statistics alongside thematic analysis. Instrument validity and reliability were established through expert review, pilot testing, and Cronbach’s alpha (α > 0.70). Ethical standards were observed throughout the study. Findings revealed that ICT integration positively influenced teaching effectiveness (75%, β = 0.62, p < 0.01), students’ learning outcomes (70%, r = 0.58, p < 0.01), learner motivation (82%, t = 4.31, p < 0.001), and classroom engagement (78%, χ² = 12.45, p < 0.01). However, only 60% of respondents reported improved educational equity, with regression results indicating a weaker association between ICT use and equity outcomes (β = 0.29, p > 0.05), reflecting persistent disparities in access to digital resources. The study concludes that ICT enhances teaching and learning when supported by adequate infrastructure, teacher competence, and institutional leadership. It recommends sustained investment in ICT infrastructure, continuous teacher professional development, strengthened instructional leadership, and equitable access to digital technologies.